STRATEGI BERTAHAN HIDUP BURUH TANI SAWIT SETELAH REPLANTING DI DESA BANJAR PANJANG KECAMATAN KERUMUTAN KABUPATEN PELALAWAN - Dewi Niswatul Chairiyah; T. Romi Marnelly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study intends to explain the survival strategy of farm workers after replanting. The replanting that look place in Banjar Panjang Village had a great impact on everylevel of society who depended on oil palm plantations daily. One of them is the farm laborers themselves, the harvesting farm workers in Banjar Panjang village after the replanting.  Of course, have to spin their brain and think a head about the future of their work. In the replanting program in Banjar Panjang Village, it is true that harvesting farm laborer after that gets a job in the a job agricultural sector to plant palm oil, but this does not apply to all harvesting farm workers.  Of the many harvesting farm workers who were selected 22 people, the rest were forced to look fot other job after replanting. Here, the researchers want to see how the socio-economic conditions of harvesting farm workers after replanting do not get job in agriculture and how to survival strategies. The research was conducted with purposive sampling technique, from this technique the researcher got 4 repondens who fit the specific criteria according to what  the recearcher wanted to convey. This study uses a qualitative method with a descriptive approach, the theory used in this study is a theory of survival strategy. Keyword: replanting, socio-economic, farm labor survival strategy